2007
DOI: 10.1111/j.1467-8543.2007.00601.x
|View full text |Cite
|
Sign up to set email alerts
|

Collective Bargaining and Wage Dispersion in Europe

Abstract: The level at which collective bargaining takes place is usually considered important in determining wage levels and wage inequalities. Two different situations are considered: a first in which bargaining is only 'multi-employer', and a second in which it is 'multi-level', in the sense that workers can be covered by both a 'multi-employer' and a 'single-employer' contract at the same time. The purpose of this paper is to analyse the impact of these different institutional settings on pay dispersion. The study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0
6

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 25 publications
3
41
0
6
Order By: Relevance
“…Indeed, wage bargaining occurs at different levels: national, sectoral, regional and/or local. Several studies have shown that the level of collective wage bargaining has an impact on the dispersion of wages within and between establishments (Dell'Aringa and Lucifora, 1994; Dominguez and Gutierrez, 2004;Plasman et al, 2005;Card and de la Rica, 2006;Dell'Aringa and Pagani, 2007). However, there is no consensus about the sign of this effect.…”
Section: Theorymentioning
confidence: 84%
“…Indeed, wage bargaining occurs at different levels: national, sectoral, regional and/or local. Several studies have shown that the level of collective wage bargaining has an impact on the dispersion of wages within and between establishments (Dell'Aringa and Lucifora, 1994; Dominguez and Gutierrez, 2004;Plasman et al, 2005;Card and de la Rica, 2006;Dell'Aringa and Pagani, 2007). However, there is no consensus about the sign of this effect.…”
Section: Theorymentioning
confidence: 84%
“…4 Ce résultat est obtenu pour la plupart des pays analysés, 5 c'est-à-dire l'Allemagne (Gürtzgen, 2006), la Belgique Rycx, 2003), le Danemark , l'Espagne (Card et de la Rica, 2006;de la Rica et González de San Román, 2007;Palenzuela et Jimeno, 1996;, la France (Leclaire et Petit, 2004), l'Italie (Checchi et Pagani, 2004;Dell'Aringa et Lucifora, 1994a; et le Portugal (Cardoso et Portugal, 2005;Hartog et al, 2002b , au Danemark (Plasman et al, 2007), aux Pays-Bas (Hartog et al, 2002a) et au Portugal (Hartog et al, 2002b), l'inverse est observé en Espagne (Dell'Aringa et Pagani, 2007; et en Italie (Checchi et Pagani, 2004;Dell'Aringa et Pagani, 2007). D'autres études mettent en évidence que les performances des entreprises (mesurées par les profits ou la productivité) sont davantage prises en compte dans la détermination des salaires lorsque ceux-ci sont négociés au niveau des entreprises (Gürtzgen, 2005 (Allemagne); Rusinek et Rycx, 2008 (Belgique);Cardoso et Portugal, 2005 (Portugal)).…”
Section: L'effet Sur Le Niveau Des Salairesunclassified
“…Enfin, il a été montré que les conventions d'entreprise réduisent les écarts de salaire entre firmes de régions différentes en Espagne (Dell'Aringa et Pagani, 2007; et en Italie (Dell'Aringa et Pagani, 2007) et les augmentent au Portugal (Hartog et al, 2002b).…”
Section: L'effet Sur Le Niveau Des Salairesunclassified
See 2 more Smart Citations